A Topography of the Void in the Performing Arts: Beckett, Adorno and Cage - Porta Caballe, Adria (Escritura e Imagen, 2025)
The present article can be read as the second part of “A topography of the void in the visual arts”, where it was already argued that the “void” can be considered as the central concept of “conflictual aesthetics” in general, through two examples in particular: the paintings of Yves Klein, and the sculpture of Oteiza and Chillida (especially in his dialogue with Heidegger). This article aims to carry on with this reflection by applying it now to the world of the performing arts, adding two further case studies: on the one hand, the Adornian reading of Beckett’s Endgame; and on the other, the question of “silence” in Cage’s 4’ 33’’. “Conflictual aesthetics”, as defined so far by Oliver Marchart, places “conflicto” at the centre of the application of the postfoundational political thought framework to contemporary art. However, the present article attempts to demonstrate that it is not so much the “conflicto”, but the “void”, as a prior and preceding moment that opens up such a conflict, that defines post-foundational art. With this objective in mind, we will attempt to further clarify and specify “conflictual aesthetics” as democratic aesthetics.